Microstructural investigation of steel corrosion in strain hardening cementitious composite (SHCC) - Chen, Zhitao (2021)
This paper presents a microstructural investigation of steel corrosion in strain hardening cementitious composite (SHCC) and reveals underlying mechanisms of reduced corrosion in R/SHCC. Results show that SHCC provides strong confinement to the corroded steel bar, which delays crack initiation and propagation in the cover. Upon cracking, corrosion products are accumulated inside the microcracks and fill the pathway which prevents the egress of rust, facilitates the formation of a dense rust layer, and thus reduces the ingress of aggressive ions to reach the surface of uncorroded steel bar and promotes the formation of less expandable types of rust, i.e. magnetite and goethite. All these microscopic mechanisms contribute to the corrosion reduction in R/SHCC.